Growth from birth to adulthood and peak bone mass and density data from the New Delhi Birth Cohort. - Tandon, N; Fall, C; Osmond, C; Sachdev, H; Prabhakaran, D; Ramakrishnan, L; Dey Biswas, S; Ramji, S; Khalil, A; Gera, T; Reddy, K; Barker, D; et al. (2012)
UNLABELLED: Growth in early life may predict adult bone health. Our data showed that greater height and body mass index (BMI) gain in utero and infancy are associated with higher peak bone mass, and greater BMI gain in childhood/adolescence with higher peak bone density. These associations are mediated by attained adult height and BMI. INTRODUCTION: To study the relationship of height and BMI during childhood with adult bone mineral content (BMC), areal density (aBMD) and apparent density (BMAD, estimated volumetric density). METHODS: Participants comprised 565 men and women aged 33-39 years from the New Delhi Birth Cohort, India, whose weight and height were recorded at birth and annually during infancy (0-2 years), childhood (2-11 years) and adolescence (11 years-adult). Lumbar spine, femoral neck and forearm BMC and aBMD were measured using dual X-ray absorptiometry; lumbar spine and femoral neck BMAD were calculated. RESULTS: Birth length, and height and height gain during infancy, childhood and adolescence were positively correlated with adult BMC (p≤0.01 all sites except birth length with femoral neck). Correlations increased with height from birth to 6 years, then remained constant for later height measurements. There were no associations with BMAD. BMI at birth, and during childhood and adolescence was also positively correlated with BMC (p < 0.01 all sites). BMI at 11 years, and BMI gain in childhood and adolescence, were correlated with aBMD and BMAD (p < 0.001 for all); these correlations strengthened with increasing age of BMI measurement. The associations with height and BMI in early life became non-significant after adjustment for adult height and BMI. CONCLUSIONS: Greater skeletal growth and BMI gain in utero and during infancy are associated with higher peak BMC, and greater BMI gain in childhood and adolescence is associated with higher peak aBMD and BMAD. These associations are mediated by the attainment of adult height and BMI, respectively.